Effects of a three-set tennis match on knee kinematics and leg muscle activation during the tennis serve - Fenter, B.; Marzilli, T. S.; Wang, Y. T.; Dong, X. N. (Perceptual and Motor Skills, 2017)
The purpose of this study was to determine the effect of a three-set tennis match on knee kinematics and leg muscle activation during the tennis serve in a real-time environment. Motion capture data and wireless electromyography of hamstrings and quadriceps muscles were collected from the back leg during the serve. A reduction of maximum knee flexion angle and a decrease of electromyography amplitudes in leg muscles were observed during the match. However, the knee angular velocity and the electromyography frequency of leg muscles remain unchanged throughout the match. The intermuscular compensation strategy to counteract fatigue might explain that the knee angular velocity was maintained despite reductions in knee flexion angle and electromyography activity of leg muscles. ABSTRACT FROM AUTHOR